1946
DOI: 10.5254/1.3546797
|View full text |Cite
|
Sign up to set email alerts
|

The Cold-Compression sets of Natural and Synthetic Vulcanizates

Abstract: The behavior of certain large synthetic rubber gaskets on naval vessels during the past winter points to the necessity for a cold compression-set test in the specifications for these gaskets. It has been found, for example, that Neoprene gaskets on large valves, which perform satisfactorily at temperatures of 60° F and above, are not usable at temperatures of 40° F and below. They take a cold compression-set, while the valves are closed, so that when the valves are opened and then again closed, the leading edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1963
1963
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The observed set is not permanent. As already noticed by Morris et al [2], putting the cold CS specimens back to the ambient condition leads to relatively quick (10-20 min) restoration of the major portion of their original shapes. More quantitative CS experiments at various temperatures down to -30 °C followed.…”
Section: Strain Recovery and Compression Set Preliminary Compression Set (Cs) Experiments In A Freezing Cabinet Indicate That The Studiedsupporting
confidence: 58%
See 1 more Smart Citation
“…The observed set is not permanent. As already noticed by Morris et al [2], putting the cold CS specimens back to the ambient condition leads to relatively quick (10-20 min) restoration of the major portion of their original shapes. More quantitative CS experiments at various temperatures down to -30 °C followed.…”
Section: Strain Recovery and Compression Set Preliminary Compression Set (Cs) Experiments In A Freezing Cabinet Indicate That The Studiedsupporting
confidence: 58%
“…Despite its importance in many practical applications, the elastic recovery or set properties at low temperatures are covered rather scarcely in academic literature. Morris et al [2] reported high compression set values for several rubber systems exposed to cold environment and noticed that the set effect is reversible upon warming to the ambient temperature. Similar effects of low temperatures on the elastic recovery in styrene butadiene rubber (SBR) and nitrile butadiene rubber (NBR) were later described in [3].…”
Section: Introductionmentioning
confidence: 99%